2004
DOI: 10.1139/g04-072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship among cultivated and wild grapevine accessions from Tunisia

Abstract: We have used nuclear and chloroplast molecular markers to genotype cultivated and wild accessions of Vitis vinifera L. from Tunisia and assess their genetic relationships. Fifty-five distinct genotypes were identified among 80 cultivated accessions, including 18 genotypic groups containing between 2 and 5 accessions per group. They could represent a total of 60 distinct cultivars owing to berry colour variation found within identical genotype groups. Most of the 55 genotypes represent unique table grape genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 9 publications
4
21
0
Order By: Relevance
“…Similarly, previous studies have reported that VVS2 (Fatahi et al 2003, Núñez et al 2004, Şelli et al 2007) and VVMD28 generate the highest number of alleles (Vouillamoz et al 2006(Vouillamoz et al , Şelli et al 2007). Other studies, including ours, have also reported that VrZAG83 generates the lowest number of alleles (Sefc et al 2000, Snoussi et al 2004 (Table 2). …”
Section: Ssr Analysissupporting
confidence: 68%
“…Similarly, previous studies have reported that VVS2 (Fatahi et al 2003, Núñez et al 2004, Şelli et al 2007) and VVMD28 generate the highest number of alleles (Vouillamoz et al 2006(Vouillamoz et al , Şelli et al 2007). Other studies, including ours, have also reported that VrZAG83 generates the lowest number of alleles (Sefc et al 2000, Snoussi et al 2004 (Table 2). …”
Section: Ssr Analysissupporting
confidence: 68%
“…However, the allele richness detected in the nuclear SSR loci and the high heterozygosis of grapevine clones render this analyses less efficient when the aim is the definition of genetic relatedness among large groups of cultivars Imazio et al 2006). Cp-SSR markers, on the contrary, proved to be particularly useful in the study of cultivar origin (Arroyo et al 2002; Palmé and Vendramin 2002;Snoussi et al 2004). A general conclusion was that the use of Cp-SSRs in the study of domesticated grapevine revealed an increase in haplotype number from East to West, suggesting that grapevine diversity is higher in the Mediterranean basin.…”
Section: Discussionmentioning
confidence: 99%
“…Snoussi et al (2004) obtained 66 alleles (7 alleles per locus) in the analysis of 80 accessions of table grape Tunisian cultivars with nine SSR markers. Snoussi et al (2004) obtained 66 alleles (7 alleles per locus) in the analysis of 80 accessions of table grape Tunisian cultivars with nine SSR markers.…”
Section: Level Of Diversity In the Moroccan Groupmentioning
confidence: 99%